Level of Understanding of Pre-School Teachers on Child Rights Fulfillment and Protection at Paud Unit in Gunung Talang Sub-District, Solok Regency, West Sumatra - Gustina, Hera; Puridawaty , Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research is based on the unknown level of understanding of PAUD teachers about the fulfillment of children's rights and protection in the PAUD Unit of Gunung Talang Sub-district. Quantitative descriptive research with the method used is the survey method. The subjects of this study were PAUD teachers in Gunung Talang Sub-district, totaling people. The instrument in this study used a Yes-No choice test where the data analysis technique used Rasch Model analysis. The Rasch model uses the principle of probability on each available option which in classical test theory is preferred to the total score of the results of the test or questionnaire. The results showed that the level of understanding of PAUD teachers about the fulfillment of children's rights and protection in the PAUD Unit of Gunung Talang Subdistrict was in the "low" category of 51.31%, "medium" of 40.79%, and "high" of 7.9%. Based on the average value, which is 3.28%, the level of understanding of PAUD teachers about the fulfillment of the rights and protection of children in the PAUD Unit of Gunung Talang Sub-district, Solok District, West Sumatra is in the "low" category.